Artificial intelligence adoption in a competitive market. (12th January 2023) - Gans, Joshua S.
Abstract: Economists have often viewed the adoption of artificial intelligence (AI) as a standard process innovation where we expect that efficiency will drive adoption in competitive markets. This paper models AI based on recent advances in machine learning that allow firms to engage in better prediction. Focusing on prediction of demand, it is demonstrated that AI adoption is a complement to variable inputs whose levels are altered directly by predictions and whose use is economized by them (that is, labour). It is shown that in a competitive market, this increases the short‐run elasticity of supply and may or may not increase average equilibrium prices. Generically, there are externalities in adoption, with this reducing the profits of non‐adoptees when variable inputs are important, and increasing them otherwise. Thus AI does not operate as a standard process innovation, and its adoption may confer positive externalities on non‐adopting firms. In the long run, AI adoption is shown to lower prices generally and raise consumer surplus in competitive markets.